Strategi Upaya Peningkatan Pendapatan Bisnis Coffee Shop Di Kota Pontianak Pasca PPKM Dimasa Covid-19 - Jaurino, Jaurino; Setiawan, Aris; Rawa, Ricola Dewi; Hendharsa, Anggra (Universitas Nusantara PGRI Kediri, 2023)
The Coffee Shop business is quite promising in Pontianak City, this is shown by the mushrooming of people drinking Coffee in cafes. The policy of implementing PPKM during the Covid –19 Pandemic made the Coffee Shop business messy, this was because they lost a lot of their customers which could lead to bankruptcy. This PKM was implemented in a Coffee shop business in Pontianak City. The method used in implementing this PKM is direct assistance to partners. The result of this PKM implementation is that various strategies can be used to revive the Coffee Shop business. Managerial strategies that can be carried out include improving customer service by providing offers to prospective customers in groups. Offer Coffee drink products in gold to loyal customers because loyal customers have limited time to enjoy drinking Coffee at the café. On the other hand, Coffee Shop business people are educated to be able to prepare Coffee bean ingredients which are processed into Coffee powder in the framework of Product Diversification.